The transition to hospital consultant and the influence of preparedness, social support, and perception: A structural equation modelling approach. (April 2013) - Westerman, Michiel; Teunissen, Pim W.; Fokkema, Joanne P.I.; van der Vleuten, Cees P.M.; Scherpbier, Albert J.J.A.; Siegert, Carl E.H.; Scheele, Fedde
<x xml:space="preserve">Abstract</x> Background: Insight into the transition from specialist registrar to hospital consultant is needed to better align specialty training with starting as a consultant and to facilitate this transition. Aims: This study investigates whether preparedness regarding medical and generic competencies, perceived intensity, and social support are associated with burnout among new consultants. Method: A population-based study among all 2643 new consultants in the Netherlands (all specialties) was conducted in June 2010. A questionnaire covering preparedness for practice, intensity of the transition, social support, and burnout was used. Structural equation modelling was used for statistical analysis. Results: Data from a third of the population were available (32% n = 840) (43% male/57% female). Preparation in generic competencies received lower ratings than in medical competencies. A total of 10% met the criteria for burnout and 18% scored high on the emotional exhaustion subscale. Perceived lack of preparation in generic competencies correlated with burnout (r = 0.15, p < 0.001). No such relation was found for medical competencies. Furthermore, social support protected against burnout. Conclusions: These findings illustrate the relevance of generic competencies for new hospital consultants. Furthermore, social support facilitates this intense and stressful stage within the medical career.